Role of lactic acid bacteria on the yogurt flavour: A review. (18th December 2017) - Chen, Chen; Zhao, Shanshan; Hao, Guangfei; Yu, Haiyan; Tian, Huaixiang; Zhao, Guozhong
ABSTRACT: Considerable knowledge has been accumulated on the lactic acid bacteria (LAB) that affect the aroma and flavour of yogurt. This review focuses on the role of LAB in the production of flavour compounds during yogurt fermentation. The biochemical processes of flavour compound formation by LAB including glycolysis, proteolysis, and lipolysis are summarised, with some key compounds described in detail. The flavour-related activities of LAB mostly depend on the species used for yogurt fermentation, and some strategies have been developed to obtain more control of the flavour-forming process. Metabolic engineering can be a powerful tool to reroute the metabolic flux towards the efficient accumulation of the desired flavour compounds with the knowledge of the complex network of flavour-forming pathways and the availability of genetic tools. Further progress made in the omics-based techniques and the use of systems biology approaches are needed to fully understand, control, and steer flavour formation in yogurt fermentation processes.